Membrane bound O-acyltransferases and their inhibitors - Masumoto,N; Lanyon-Hogg,T; Rodgers,UR; Konitsiotis,AD; Magee,AI; Tate,EW (Biochemical Society Transactions, 2015)
Since the identification of the membrane-bound O-acyltransferase (MBOATs) protein family in the early2000s, three distinct members [porcupine (PORCN), hedgehog (Hh) acyltransferase (HHAT) and ghrelin Oacyltransferase(GOAT)] have been shown to acylate specific proteins or peptides. In this review, topologydetermination, development of assays to measure enzymatic activities and discovery of small moleculeinhibitors are compared and discussed for each of these enzymes.